The Role of Meaningful Work and Employee Well-being on Employee Experience: Moderation by Employee Autonomy - Literature Review - Edigar Filipe Pereira; Miswanto Miswanto; Frasto Biyanto; Baldric Siregar; Anacleto Roberto Carolina Soares; Filipe Mendes Pereira (International Journal of Islamic Business and Management Review, 2024)
This study examines the moderating effect of employee autonomy on the relationship between meaningful work and employee well-being in the context of employee experience. A literature review was used, combined with meta-analysis, to examine 95 publications from Scopus-indexed journals published between 2014 and 2023. The findings indicate that employee autonomy significantly moderates the relationship between meaningful work and employee well-being, which positively influences employee experience. In addition, employee well-being is identified as the most substantial factor affecting employee experience, followed by employee autonomy and meaningful work. This study emphasizes the importance of organizations providing autonomy to employees to improve their overall well-being and work experience. Theoretical and practical implications are emphasized for human resource management, especially in formulating policies that enhance employee engagement through meaningful work and empowerment. Future studies should investigate moderating factors, including organizational culture and leadership style, in more depth.